2013
DOI: 10.5152/dir.2013.13275
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of minimum apparent diffusion coefficient with maximum standardized uptake on fluorodeoxyglucose PET-CT in patients with rectal adenocarcinoma

Abstract: ABDOMINAL IMAGINGORIGINAL ARTICLE PURPOSE The aim of this study was to retrospectively assess the correlation between minimum apparent diffusion coefficient (ADC min ) values obtained from diffusion-weighted magnetic resonance imaging (MRI) and maximum standardized uptake values (SUV max ) obtained from positron emission tomography-computed tomography (PET-CT) in rectal cancer. MATERIALS AND METHODSForty-one patients with pathologically confirmed rectal adenocarcinoma were included in this study. For preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…To the best of our knowledge, our study is the first that confirms an association between the tumor cellularity and the metabolic activity both in pathological lymph nodes and the related untreated LARC. 11 , 12 ADCmin and ADCmean did not, however, help differentiate pathological from benign lymph nodes.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…To the best of our knowledge, our study is the first that confirms an association between the tumor cellularity and the metabolic activity both in pathological lymph nodes and the related untreated LARC. 11 , 12 ADCmin and ADCmean did not, however, help differentiate pathological from benign lymph nodes.…”
Section: Discussionmentioning
confidence: 69%
“…However, we found a statistically significant negative correlation between ADCmean and the corresponding SUVmean values (ρ = −0.61, P = 0.0017) and between ADCmin and SUVmax (ρ = −0.66, P = 0.0005) values. Two previous studies 11 , 12 have shown a significant negative correlation between ADCmin and SUVmax ( r = −0.450, P = 0.009; and r = −0.347, P = 0.026, respectively) for primary rectal adenocarcinoma. In these studies, ADCmin was determined as the lowest value and SUVmax as the highest value among all voxels of the entire volume in each tumor.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Colakoglu et al (28) reported a significant negative correlation between minimum ADC and SUVmax in rectal cancer. In addition, a few previous studies have shown that minimum ADC in the tumor showed strong correlation with high cellularity (20,29).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies found negative associations between SUV max and ADC values ( 34 , 35 ). However, in our study, no significant linear correlations were found between the investigated parameters.…”
Section: Discussionmentioning
confidence: 99%